(untitled) (Italian Journal of Public Health, 2012)
Background: infectious low pathogenic avian influenza viruses (LPaIVs) have been recently detected on feathers of wild ducks. Laboratory trial results suggested that the preen oil gland secretion, covering waterbirds’ feathers, may attract and concentrate virus particles from aIV-contaminated waters to birds’ bodies. We evaluated whether ducks can become infected by the ingestion of preen oil-associated viral particles, experimentally smeared on their plumage. In addition, we compared virologic and serologic results obtained from mallards whose feathers were experimentally infected, with those from wild mallards naturally carrying aIVs on feathers. Methods: we experimentally coated 7 mallards (anas plathyrynchos) using preen oil mixed with a LPaIV (h10n7 subtype), and housed them for 45 days with a control, uncoated duck. cloacal, oropharyngeal and feather swabs were collected from all birds and examined for aIV molecular detection and isolation. Blood samples were also taken to detect influenza specific antibodies. In addition, sera from 10 wild mallards, carrying on feathers infectious LPaIV h10n7, were examined. Results: virologic and serologic results indicated that through self- and allopreening all the birds experimentally coated with the preen oil/aIV mix and the control duck ingested viruses covering feathers and became infected. Virus isolation from feathers was up to 32 days post-coating treatment. one out of 8 wild mallards showing antibodies against type a influenza virus was seropositive for h10 subtype too. Conclusions: our experimental and field results show evidences suggesting that uninfected birds carrying viruses on their feathers, including immune ones, might play an active role in spreading aIV infection in nature. For this reason, routine aIV surveillance programs, aimed at detecting intestinal and/or respiratory viruses, should include the collection of samples, such as feather swabs, enabling the detection of viruses sticky to preened birds’ bodies....